2014
DOI: 10.1016/j.neuropharm.2014.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Prior stimulation of the endocannabinoid system prevents methamphetamine-induced dopaminergic neurotoxicity in the striatum through activation of CB2 receptors

Abstract: Methamphetamine toxicity is associated with cell death and loss of dopamine neuron terminals in the striatum similar to what is found in some neurodegenerative diseases. Conversely, the endocannabinoid system (ECS) has been suggested to be neuroprotective in the brain, and new pharmacological tools have been developed to increase their endogenous tone. In this study, we evaluated whether ECS stimulation could reduce the neurotoxicity of high doses of methamphetamine on the dopamine system. We found that metham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 77 publications
1
19
0
Order By: Relevance
“…The neuroprotective effect of JZL184 has been demonstrated in animal models of Parkinson's disease [28,11] and in methamphetamine-induced toxicity in mice [29] both affecting the dopaminergic system. However, no neuroprotective effect has been reported in an animal model of malonateinduced neurotoxicity and in M-213 cells, which have a phenotype similar to striatal neurons [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuroprotective effect of JZL184 has been demonstrated in animal models of Parkinson's disease [28,11] and in methamphetamine-induced toxicity in mice [29] both affecting the dopaminergic system. However, no neuroprotective effect has been reported in an animal model of malonateinduced neurotoxicity and in M-213 cells, which have a phenotype similar to striatal neurons [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the effect of rimonabant in mitochondrial CB 1 receptors that regulate energy metabolism in neurons [38]. CB 2 receptors are involved in neuroprotection under different pathological conditions [39][40][41][42]29] including an animal model of Parkinson's disease [16]. In general, the protective role of CB 2 receptor activation is mostly attributed to its ability to reduce deleterious microglial activation [43,44,39,40], although CB 2 -mediated regulation of astroglial phenotype could also support the neuroprotective effect [45].…”
Section: Discussionmentioning
confidence: 99%
“…Converging evidence suggests that endogenous cannabinoids also play a neuroprotective role in pathological situations [ 143 ]. Indeed, administration of a toxic dose of methamphetamine alters striatal levels of endocannabinoids, the endogenous ligands of CB 1 and CB 2 receptors, and inhibition of the hydrolysis of these compounds prevents METH-induced reduction of tyrosine hydroxylase levels, a hallmark of dopamine terminal loss in the striatum [ 144 ]. Recent research found that METH altered the levels of the major endocannabinoids, anandamide (AEA), and 2-arachidonoyl glycerol (2-AG) in the striatum, suggesting that the ECS participated in the brain responses to METH [ 7 ].…”
Section: Treatment Of Neurotoxicitymentioning
confidence: 99%
“…It was suggested that the neuroprotective effect of AEA is mediated by CB1 and CB2 receptors [15] , whereas both cannabinoid receptor dependent [10] and independent [16] effects of AEA on microglial activity were reported. Increased AEA levels were observed in neurodegenerative and neuroinflammatory disorders [17] , which is probably neuroprotective, since cannabinoid system activity is thought to be anti-inflammatory and protective in Parkinson disease [18] , Alzheimer disease [19] , multiple sclerosis [20] and traumatic brain injury [21] .…”
Section: Introductionmentioning
confidence: 99%